The Intellectual Property Rights of the Batak Toba Ethnicity - Dina Andiza; Siti Nurhayati (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Intellectual Property Rights (IPR) are rights to property that arise and are born from human intellectual abilities. Whereas Communal Intellectual Property (KIK) is the result of copyrights, works, and cultural traditions that have been passed down from generation to generation by a group of people. Communal Intellectual Property includes Traditional Knowledge (PT), Traditional Cultural Expressions (EBT), Genetic Resources (SDGs), and Geographical Indications (GI). The purpose of this study is to study of Intellectual Property Rights in Indonesia and to determine the role of the Regional Government in protecting and guaranteeing the Communal Intellectual Property of the Batak Toba ethnicity. This type of thesis research uses normative legal research with a qualitative approach method, the research method used, namely Library Research, with data collection techniques using Secondary Data which is divided into Primary Legal Materials, Secondary Legal Materials and Tertiary Legal Materials. The efforts to know about the Batak Toba KIK are based on a statutory regulation, namely Law Number 28 of 2014 concerning Copyright and the efforts of the Regional Government to protect and develop the Batak Toba KIK by registering it with the Directorate General of Intellectual Property (DJKI). Suggestions from researchers are that Batak Toba KIK can be protected by establishing separate KIK laws and regulations, forming a KIK handling group in the midst of society and changing the concept of Batak Toba people's thinking about preserving and protecting Batak Toba ethnic KIK